EFFECTS OF FARMERS’ KNOWLEDGE, ATTITUDE, SKILLS ON HIGHLAND MAIZE ADOPTION IN WESTERN ETHIOPIA - Soruma Gerbi; Berhanu Megerssa (Socio-Economics/Agribusiness Department, 2020)
Understanding farmers' indigenous knowledge is vital in hybrid maize popularization. Despite different opportunities, adoption was constrained by the failure of infusing local knowledge in the modern extension system. Hence, farmers' capabilities, preferences, and practices towards adoption were studied. Data were collected from key informants and focus group discussion participants. A cross-sectional survey was to collect data from 154 respondents. Knowledge and attitude were assessed by using a 5-point Likert scale. Descriptive statistics and econometric analyses were run to analyze data accordingly. The results indicated among demographic characteristics; family and land size, owning of ox and experience have positively affected highland maize adoption at 1 per cent significance level; while education, age, and on-farm income have positively affected highland maize adoption at a 1% significance level. However, religion and sex did not affect highland maize adoption at all. Pearson chi-square result indicated, there was a positive and significant relationship of knowledge (χ2=41.49; p=0.000) to adoption. Consequently, an increase in farmers' knowledge of favoured adoption. Finally, poor institutional support, insufficient involvement of resource-poor farmers, and lack of training were major bottlenecks hampering highland maize adoption. Hence, provision of special training, credit services, and farmers-responsive training should be in place for better adoption.